2018
DOI: 10.1016/j.mechrescom.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Optimal bone structure is dependent on the interplay between mechanics and cellular activities

Abstract: Bone is a tissue with the remarkable capacity to adapt its structure to an optimized microstructural form depending on variations in the loading conditions. The remodeling process in bone produces distinct tissue distributions such as cortical and trabecular bone but also fibrous and cartilage tissues. Although it has been demonstrated that mechanical factors play a decisive role in the architectural optimization, it may also follow that biological factors have an influence. This interplay between loading and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…More importantly, this is a way to take into account the accumulation of damage and micro-cracks taking part in the bone remodeling process ( Carter et al, 1988 ; Mori and Burr, 1993 ; Prendergast and Taylor, 1994 ; Doblaré et al, 2002 ; Martin and Seeman, 2008 ). Previous computer models of bone remodeling based on strain accumulation have been able to predict the femur head bone density distribution ( Frame et al, 2018 ) and healing patterns in a mandible ( Schmitt et al, 2016 ); however, other mechanical signals have also proven to be valid, e.g., the strain energy density ( Schulte et al, 2013 ). In general, a consensus about the mechanical stimulus driving the bone remodeling process does not exist ( Webster and Müller, 2011 ; Weinkamer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, this is a way to take into account the accumulation of damage and micro-cracks taking part in the bone remodeling process ( Carter et al, 1988 ; Mori and Burr, 1993 ; Prendergast and Taylor, 1994 ; Doblaré et al, 2002 ; Martin and Seeman, 2008 ). Previous computer models of bone remodeling based on strain accumulation have been able to predict the femur head bone density distribution ( Frame et al, 2018 ) and healing patterns in a mandible ( Schmitt et al, 2016 ); however, other mechanical signals have also proven to be valid, e.g., the strain energy density ( Schulte et al, 2013 ). In general, a consensus about the mechanical stimulus driving the bone remodeling process does not exist ( Webster and Müller, 2011 ; Weinkamer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This model improved the understanding of bone fracture remodeling and suggested that this healing stage can be explained by an accumulation of mechanical strains, namely that the loading history over a few hours can account for observed tissue patterning and remodeling. Previously, the model has been shown to explain bone remodeling in the femoral head ( Frame et al, 2018 ) and in the mandible ( Schmitt et al, 2016 ). Future work should take advantage of this model to investigate impaired healing situations or non-unions, e.g., due to osteoporosis or other co-morbidities, and evaluate the validity of the model in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to more precisely address this bone remodeling process from the simulation prediction point of view, one must account for both the mechanics (external forces applied to the structure) and the independent cell activity that are at play within the bone structure. A non-exhaustive list of the main influencing parameters for bone remodeling includes cell migration and differentiation, together with their interplay with their mechanical environment [28][29][30][31][32]. In addition, the mechanics should be coupled with the biology into a common bone "stimulus" leading the bone remodeling [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, trying to optimize the knowledge of the links between the mechanical forces and the biological reactions (Stoltz et al 2018), a number of mechanobiological models were developed (George et al 2018(George et al , 2019. Some models try to take into account the bone cells activity both at the local (Lemaire et al 2011) and at the global (Frame et al 2018) scales. However, bridging between these two scales remains challenging (Sheidaei et al 2019;Bagherian et al 2020).…”
Section: Introductionmentioning
confidence: 99%